2021
DOI: 10.25270/wnds/2021.161168
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cellular- and/or Tissue-Based Therapy for the Management of Pyoderma Gangrenosum: A Case Series and Review of the Literature

Abstract: Pyoderma gangrenosum (PG) is an uncommon inflammatory neutrophilic disorder with a spectrum of clinical presentations with variable courses. Most cases are associated with an autoimmune disorder and manifest in middle-aged adults as a painful lesion that progresses to painful necrotizing ulcers of the lower extremity. Owing to its variability, clinical diagnosis remains difficult and many patients are often misdiagnosed, with resulting delay in treatment. While early immunosuppressant therapy is key to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Chan et al reported a case in which a PG lesion secondary to ulcerative colitis was treated with a fetal bovine dermis (FBD) graft [ 64 ]. The FBD was bolstered with nonadherent cellulose acetate mesh and wrapped with a zinc oxide compression boot.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al reported a case in which a PG lesion secondary to ulcerative colitis was treated with a fetal bovine dermis (FBD) graft [ 64 ]. The FBD was bolstered with nonadherent cellulose acetate mesh and wrapped with a zinc oxide compression boot.…”
Section: Reviewmentioning
confidence: 99%
“…The wound bed showed near-complete response at the one-month follow-up. Authors concluded that surgical intervention combined with immunosuppressive therapy can aid in wound healing and should be considered for extensive wounds [ 64 ].…”
Section: Reviewmentioning
confidence: 99%